Κ-carrageenan-C-phycocyanin based smart injectable hydrogels for accelerated wound recovery and real-time monitoring. (June 2020) - Dev, Atul; Mohanbhai, Soni Jignesh; Kushwaha, Avinash Chandra; Sood, Ankur; Sardoiwala, Mohammed Nadim; Choudhury, Subhasree Roy; Karmakar, Surajit
Abstract: Wound healing remains a healthcare challenge in patients suffering from grave tissue damage due to burn injuries and severe medical conditions like diabetes and ischemia. A repeated wound dressing in such cases leads to tissue damage, which could further inflate the wound healing. It is also challenging to analyze the depth of wound bed in these conditions, which could affect the recovery period. To address this need, we have developed an injectable hydrogel from natural polysaccharide κ-carrageenan and a pigmented protein C-phycocyanin. C-phycocyanin has wound healing, antimicrobial, antioxidant and anti-inflammatory properties along with the In-vivo fluorescence imaging ability. Gelling property of κ-carrageenan could be utilized along with C-phycocyanin as an injectable and regenerative wound dressings matrix to monitor wound healing in real-time without upsetting the healing process. The hydrogel presented herein was built from ionic crosslinking of κ-carrageenan monomers along with C-phycocyanin, which provides an interconnected network of porous material with hydrophilic surface and mechanical stiffness. This porosity allows nutrients transportation and gaseous exchange across the wound healing site for the proliferation of various cells. Hydrogel material enhances the proliferation of dermal fibroblasts in vitro without inducing inflammation along with reducing the blood clotting time with no haemolysis. We have found that κ-carrageenan-C-phycocyanin (κ-CRG-C-Pc) hydrogel not only exhibit superior haemostatic capabilities in traumatic injury condition but also provide support for rapid wound healing. Overall, these findings demonstrate the potential of κ-carrageenan-C-phycocyanin hydrogels as a wound-healing and imaging platform towards accelerating tissue repair and real-time monitoring. Statement of Significance: Blood clotting and inflammation are the most crucial stages of wound healing along with appropriate monitoring of the healing process. Thus, there is a need of system that could provide point-to-point care and monitoring in this multistage process. Here, we have introduced a self healing, injectable hydrogel system with in vivo imaging abilities from κ-carragenan and C-phycocyanin. C-phycocyanin improves the stability of κ-carragenan matrix and provide support to cellular adhesion, proliferation, and migration. Its anti-inflammatory response and rapid blood clotting ability further empower its applicability in critical medical conditions and wound recovery. Graphical abstract: Image, graphical abstract